The Role of Spiritual Intelligence And Self-Efficacy In Enhancing Elementary School Students' Academic Achievement: A Systematic Literature Review - Munandar, Arif; Supriyatna, Encep; Rahayu, Ida (International Conference on Elementary Education, 2025)
Modern education often overemphasizes cognitive achievement, neglecting internal student factors crucial for holistic learning success. This study aims to deeply synthesize and analyze the synergistic role of spiritual intelligence and self-efficacy in enhancing the academic achievement of elementary school students. Using a Systematic Literature Review (SLR) approach, relevant articlesfrom databases such as Google Scholar and Garuda were identified and analyzed through a rigorous selection process to map the existing evidence. The synthesis results reveal three main findings: (1) Self-efficacy consistently proves to be a strong predictor of academic achievement, functioning as the